Ajax in Oracle JDeveloper - Vohra, Deepak; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2008)
Asynchronous JavaScript and XML (Ajax) is a web technique used to transfer data between a browser and server asynchronously without posting the web page to the server. "Asynchronously" implies that the processing of the web page continues while the Ajax request is sent to the server and a response is received from the server. The web page, or section(s) of the web page, is refreshed with the Ajax response without reposting the web page. Ajax has the following advantages over non-Ajax web applications. - Reduced response time and reduced server load, as the complete web page is not reposted. - Reduced bandwidth of web applications as only data is transferred and the HTML format is applied in the browser. - Separation of data, format and style. The book covers web search and RSS Feed with Ajax as well as form validation with Ajax frameworks for Java, JSP, JSF, and PHP. It discusses using Ajax in Oracle JDeveloper and is IDE based. JDeveloper has the following advantages over Eclipse IDE. - JDeveloper 11g provides an integrated JavaScript Editor for Ajax/Web development. - It also provides a PHP extension. - JDeveloper has a built-in support for JSF and for JDBC.
What is Ajax? -- Developing an Ajax Web Application -- Less JavaScript with Prototype -- Ajax with Java-GWT -- Ajax with Java-DWR -- Ajax without JavaScript $1 (BAjaxTags -- Ajax with JSF-Ajax4jsf -- Ajax with PHP-Xajax -- RSS Feed with Ajax -- Web Search with Ajax.s
Keywords: Computer science; Software engineering; Operating systems (Computers).; Computer Science; Software Engineering/Programming and Operating Systems; Information Systems Applications (incl. Internet).; Operating Systems; Electronic books